Novedades en la Amazonía peruana - Gómez, Luis Diego (Lankesteriana: International Journal on Orchidology, 2006)
The aquatic plant Phyllanthus fluitans Benth. ex Müll. Arg. (Phyllanthaceae) is reported from the Ucayali, Napo, and Amazon rivers. An unusual form of Anetium citrifolium (L.) Splitg. (Vittariaceae) is here described as a new variety.